The complete works of Joyce Wieland 1963-1986 - Wieland, Joyce 1931-1998; Pringle, Douglas ca. 20. Jh (CFMDC, 2011)
"A young woman marries a wealthy man she isn't in love with, but finds romance instead with the couples' painter friend." [imdb.com]
Original: Kanada 1976
study guide by Johanne Sloan
Keywords: Film; DVD-Video